Reformasi Pelayanan Publik Sebagai Strategi Mewujudkan Good Governance - Muhammadiah Muhammadiah (Otoritas : Jurnal Ilmu Pemerintahan, 2011)
System of government with good governance paradigm is intended to further promote the involvement of all stakeholders in governance. In practical terms, the challenge of good governance paradigm will be faced with the demands of society in improving the quality of public services. Public service practices that are conducive to stimulating real and public participation to further improve the implementation of good governance. so many public service activities that feel a lack of good public service, so that all parties are less optimistic about the realization of good governance in Indonesia. A country with a high heterogeneity conditions in a variety of things such as ethnic, cultural, geographical, religious, and socio-economic development level, is a considerable potential as a source of conflict, and can lead to national disintegration. Development of civil society requires a public space (public sphere) in which every citizen could freely and independently express opinions about various social problems. Transparency of information and public service is fundamental in the governance demands that the principle of good governance, in which required the disclosure of information as one of the implementation requirements of public accountability.Sistem pemerintahan dengan paradigma pemerintahan yang baik dimaksudkan untuk lebih mempromosikan keterlibatan semua pemangku kepentingan dalam pemerintahan. Dalam istilah praktis, tantangan paradigma pemerintahan yang baik akan dihadapkan dengan tuntutan masyarakat dalam meningkatkan kualitas pelayanan publik. Pelayanan publik praktek-praktek yang kondusif untuk merangsang partisipasi yang nyata dan masyarakat untuk lebih meningkatkan pelaksanaan pemerintahan yang baik. begitu banyak kegiatan pelayanan publik yang merasa kurangnya layanan publik yang baik, sehingga semua pihak yang kurang optimis tentang realisasi pemerintahan yang baik di Indonesia. Sebuah negara dengan kondisi heterogenitas yang tinggi dalam berbagai hal seperti tingkat perkembangan etnis, budaya, geografis, agama, dan sosial-ekonomi, adalah potensi besar sebagai sumber konflik, dan dapat menyebabkan disintegrasi nasional. Pengembangan masyarakat sipil membutuhkan ruang publik (ruang publik) di mana setiap warga negara bisa secara bebas dan mandiri mengekspresikan pendapat tentang berbagai masalah sosial. Transparansi informasi dan pelayanan publik adalah fundamental dalam tuntutan pemerintahan yang prinsip pemerintahan yang baik, di mana diperlukan keterbukaan informasi sebagai salah satu persyaratan pelaksanaan akuntabilitas publik.